FOREIGN ACTIVITY OF A COMPANYAS A SUBJECT OF THE WORLD ECONOMY - Andrey F. Shadrin (Статистика и экономика)
The article describes the necessity of having a foreign economic activity for a company in a globalized economy. The article also describes how to implement foreign trade activities with their features. Foreign economic activity of the company can’t be done without control by the public authorities, so article describes public authorities with their specificity to control foreign trade company activities.